Branding Kota DKI Jakarta Sebagai Kota Kreatif Bidang Sastra - Adenna Hendy Cassie Putri; Gustaf Wijaya; Santi Isnaini; Dina Septiani (Jurnal Ilmiah Wahana Pendidikan, 2023)
The city of Jakarta officially became the City of Literature, and the city officially became a member of the UNESCO Creative Cities Networks. The decision to locate in Jakarta was also influenced by a number of factors. One of them is the city of Jakarta, which fosters new talent in the creation of literary works such as books or novels. Presented in new and different genres and styles to pique the interest of today's young people in reading. This study is a Content Analysis study, which is a systematic technique for assessing message content and processing communications, or a tool for observing and analyzing open communication behavior from selected communicators. Based on the findings, it is possible to conclude that city branding is one method of promoting Jakarta as a literacy city, by constructing and offering services and infrastructure such as literacy parks for the public.